Socialization Of The International Certified Internship Program In Support Of The Merdeka Belajar - Kampus Merdeka Policy At The Faculty Of Teacher Training And Education, Santo Thomas Catholic University, Medan - Geby Citra Ananda; Zuhri Ramadhan; Bambang Suwarno; Bhakti Alamsyah (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2022)
The internship program is an activity for students to apply knowledge, attitudes, general and specific skills in the workplace. The duration of this internship is a minimum of 6 months and can be extended according to the provisions or agreement between the original institution and the Internship Workplace. Students must be guided by internal supervisors from lecturers and external supervisors from the Internship Workplace. The purpose of this paper is to find and take an inventory of several businesses as partners in the implementation of student internships at the Faculty of Teacher Training and Education, Santo Thomas Catholic University, Medan. Literature research on ideas was reviewed, various literatures were collected and analyzed descriptively. This study shows that there are several businesses that can be used as student internship partners. Such as multi-language internships in Altissia - Belgium, IT Internships at Smartinternz - Singapore, Hospitality Internships in Hotels in Asia Pacific, Middle East and Australia countries, and Internships on Cruise Ships. This program is to encourage students to be able to master various competencies and this program is expected to enable students to improve the competence of graduates, both soft skills and hard skills, to be ready with the needs of the times and prepare graduates who are superior, moral and ethical.